ANTIINFLAMMATORY ACTIVITY OF LEFLUNOMIDE FOR COMBINED APPLICATION WITH СELECOXIB AND AMLODIPINE IN ADJUVANT ARTHRITIS AGAINST THE BACKGROUND OF ARTERIAL HYPERTENSION - Seredynska, N.M.; Korniyenko V.І.; Мokhort М.А.; Yeromina H.О.; Ieromina, Z.G.; Ladohubets О.V.; Duchenko, K.A. (World of Medicine and Biology, 2020)
The purpose of the work was to study the anti-edema activity of leflunomide in combination with celecoxib and amlodipine under the conditions of experimental rheumatoid arthritis associated with arterial hypertension. Experiments were carried out on sexually mature nonlinear white rats of both sexes with a starting weight of 201.56 ± 2.42; (n = 174). Experimental RA was induced by subcutaneous injection of the complete AF into the plantar part of the posterior (left) limb. The drugs under study were: leflunomide (LF), 20 mg tablets; celecoxib (CC), 100 mg capsules, and amlodipine (AM), 10 mg tablets. Under the conditions of experimental RA that developed against the background of AH, there was a significant increase in the foot volume by 136-147 % (from 1.16 RU to 2.74 RU) compared to the values in animals of the intact group. Combined application of CC with LF against the background of the combined pathology led to a significant, compared to data in animals with a combined pathology and in rats treated with LF only, reduction in foot volume by 14.4-45.2 % and by 18-41.4 % respectively at all terms of observation. Particularly significant this effect was in the acute development of AA against the background of hypertension. With combined use of leflunomide, celecoxib and amlodipine only in the acute period of inflammation that develops against the background of arterial hypertension, an anti-edema effect is recorded at the level of 12%, which is significantly reduced in other observation periods.